Differential expression of ID4 and its association with TP53 mutation, SOX2, SOX4 and OCT-4 expression levels. - Thais Fernanda de Almeida Galatro (PLoS ONE, 2013)
Inhibitor of DNA Binding 4 (ID4) is a member of the helix-loop-helix ID family of transcription factors, mostly present in the central nervous system during embryonic development, that has been associated with TP53 mutation and activation of SOX2. Along with other transcription factors, ID4 has been implicated in the tumorigenic process of astrocytomas, contributing to cell dedifferentiation, proliferation and chemoresistance. In this study, we aimed to characterize the ID4 expression pattern in human diffusely infiltrative astrocytomas of World Health Organization (WHO) grades II to IV of malignancy (AGII-AGIV); to correlate its expression level to that of SOX2, SOX4, OCT-4 and NANOG, along with TP53 mutational status; and to correlate the results with the clinical end-point of overall survival among glioblastoma patients. Quantitative real time PCR (qRT-PCR) was performed in 130 samples of astrocytomas for relative expression, showing up-regulation of all transcription factors in tumor cases. Positive correlation was found when comparing ID4 relative expression of infiltrative astrocytomas with SOX2 (r = 0.50; p<0.005), SOX4 (r = 0.43; p<0.005) and OCT-4 (r = 0.39; p<0.05). The results from TP53 coding exon analysis allowed comparisons between wild-type and mutated status only in AGII cases, demonstrating significantly higher levels of ID4, SOX2 and SOX4 in mutated cases (p<0.05). This pattern was maintained in secondary GBM and further confirmed by immunohistochemistry, suggesting a role for ID4, SOX2 and SOX4 in early astrocytoma tumorigenesis. Combined hyperexpression of ID4, SOX4 and OCT-4 conferred a much lower (6 months) median survival than did hypoexpression (18 months). Because both ID4 alone and a complex of SOX4 and OCT-4 activate SOX2 transcription, it is possible that multiple activation of SOX2 impair the prognosis of GBM patients. These observational results of associated expression of ID4 with SOX4 and OCT-4 may be used as a predictive factor of prognosis upon further confirmation in a larger GBM series.